Severe Inflammation Caused by Coinfection of PCV2 and Glaesserella parasuis Is Associated with Pyroptosis via Noncanonical Inflammasome Pathway - Jiahui An; Chao Zhang; Jinshuang Cai; Yufeng Li (Cellular Microbiology)
Coinfections of porcine circovirus type 2 (PCV2) and Glaesserella parasuis (G. parasuis) are widely existing in the swine industry worldwide. However, the mechanisms for this coinfection remain unclear. The aim of this study is to assess whether the coinfection PCV2 and G. parasuis would affect the inflammatory response and related mechanisms. In this study, BALB/c mice and RAW264.7 cells were used to study the inflammation and related mechanism caused by the coinfection of PCV2 and G. parasuis. Coinfection with PCV2 and G. parasuis significantly increased the mortality of mice and led to the development of more severe lung and spleen lesions compared with single agent infection. Especially, coinfection significantly increased the bacterial loads in the lungs. Coinfection with PCV2 and G. parasuis can enhance RAW264.7 cell phagocytosis and elimination to G. parasuis. Cell death rate of cells increased in coinfection was measured with Flow cytometry. Moreover, coinfection led to the downregulation of the expression of TNFα and IL-8 in comparison with G. parasuis infection, but the maturation of interleukin-1β (IL-1β) was significantly upregulated. Our study firstly revealed that coinfection of PCV2 and G. parasuis can increase the phagocytosis of cells to G. parasuis, and LPS in the cytoplasm will induce the maturation of caspase-11 and lead to the cleavage of Gasdermin D (GSDMD) to cause pyroptosis by noncanonical pathway. The revealing of mechanisms associated with coinfection with PCV2 and G. parasuis will provide a scientific basis for investigating the synergistic infection mechanisms between viruses and bacteria.